ANALISIS TINGKAT RISIKO DAN KERENTANAN BAHAYA GEMPA BUMI DI KOTA SURABAYA DALAM UPAYA PEMBERIAN INFORMASI MITIGASI BENCANA - Ulfa Nur Silvia; Afra Kansa Maimuna (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2020)
Surabaya segment and Waru segment, part of Baribis-Kendeng Fold Thrust Zone that passes through Surabaya City potentially affected by earthquake hazard in the future with high population that settled there and high number of buildings. The impact of earthquake hazard can be decreased by Peak Ground Acceleration (PGA), high population density, and buildings analysis as an action of mitigation. PGA value calculated by McGuire empirical formula (1974, 1977) using historical data of earthquake in the past 50 years and the result of this value among 33,991 -29,8194 gal, this result classified as low frequency related to MMI scale that released by BMKG. The map result of PGA that related to spatial data of high population and high buildings in the Surabaya conclude that east side of Surabaya has a very high risk of earthquake vulnerability.